2011
DOI: 10.1182/blood-2011-03-343657
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2 46/1 haplotype in splanchnic vein thrombosis

Abstract: References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…We found that JAK2 polymorphism was not associated with BCS susceptibility. Our observations were at variance with those reported by some researchers [ 19 , 28 ], who found that 46/1 haplotype is present more frequently in BCS patients. However, the significant difference disappeared when including portal vein thrombosis (PVT) patients.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that JAK2 polymorphism was not associated with BCS susceptibility. Our observations were at variance with those reported by some researchers [ 19 , 28 ], who found that 46/1 haplotype is present more frequently in BCS patients. However, the significant difference disappeared when including portal vein thrombosis (PVT) patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Smalberg et al [19] recently demonstrated that the 46/1 haplotype is associated with the development of JAK2 V617F-positive splenic vein thrombosis (SVT), but the existence of JAK2 V617F-negative SVT patients also indicates an important role for the 46/1 haplotype in the etiology and diagnosis of SVT-related MPNs. In contrast, Kouroupi et al [20] showed that the 46/1 haplotype is not a susceptibility locus for the development of SVT. Thus, further exploration is required to clarify whether the JAK2 germline variation is a risk factor of thrombosis.…”
Section: Discussionmentioning
confidence: 98%
“…Villani et al () replicated these findings – 46/1 haplotype was over‐represented in V617F + patients with SVT but not in the JAK2 W/T group. However, other studies disagree: Kouroupi et al () found no difference in the 46/1 haplotype frequency amongst 170 V617F + versus W/T SVT patients ( P = 0·9). These differences can partly be attributed to differences in JAK2 burdens between patients; those with lower allele burdens express 46/1 haplotype frequencies similar to V617F‐negative patients.…”
Section: Individual Risk Factors For Svtmentioning
confidence: 96%